Analisis Sudut Pandang Peserta Didik terhadap Media Belajar Daring; Studi Analisis Kebutuhan Belajar - Sandi Pradana (Departement of Mathematics Education, 2023)
The aims of this study were (1) to identify the main purpose of learning English, (2) to identify the students’ target needs and, (3) to identify the students’ learning needs of students’ grade XI in Piyungan 1 High School. This research was categorized as a survey study. The subjects of this study were XI grade senior high school students of Piyungan 1 High School and their English teacher. The students of Piyungan 1 have good standpoint toward online learning media. Internet as a medium in teaching and learning provides learners with more authentic learning environments. The students and teacher believe that online media such as weblog has certain facilities that can transform teaching and learning’s role from the teacher center to student-cantered